(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study reports the findings of survey undertaken on root rot in mulberry, a serious disease caused by fungi viz., Botryodiplodia theobromae (black rot), Macrophomina phaseolina (charcoal rot) and Fusarium spp. (dry rot) in important sericulture areas of South India. A total of 95 isolates of fungi associated with root rot were recovered from different mulberry gardens. These isolates were subjected to in-depth characterization by cultural and morphological parameters and molecular markers (RAPDs and SSRs). B. theobromae isolates showed variability in growth of mycelia, sclerotial shape and abundance and conidial size whereas, M. phaseolina exhibited variability in pycnidial abundance and conidial size. Fusarium isolates comprising of two species – F. oxysporum and F. solani revealed variability in hypha, macroconidia, microconidia and septation. Among the virulent isolates, one each of B. theobromae (BT-2) and F. solani (FS-25) recorded 100 root rot of host root system. But, in case of M. phaseolina, four isolates from Tigulahusahalli (MP-1), Peddavaram (MP-5), Parigi (MP-7) and Vellivalasa (MP-10) recorded complete root rot infection. Majority (virulent and moderately virulent) of the isolates of M. phaseolina (91.6) showed infectivity compared to B. theobrome (80) and Fusarium (72). Stepwise MRA could identify markers associated with root rot infection in Fusarium spp. (30), M. phaseolina (19) and B. theobromae (5). Among the phenotypic markers, only mycelia growth was found to be associated with rotting of roots in case of M. phaseolina. The microconidial width and pigmentation of reverse colony of Fusarium spp. were found to be associated with root rot () but, only microconidial width showed positive correlation. The grouping of isolates based on genetic analysis did not reveal correlation either with geographical distribution or pathogenicity, possibly because of the rapid fungal spread due to anthropogenic activities, thus preventing population isolation and stratification. Genetic variability and diversity in the root rot associated fungi is bewildering and may contribute to the evolution of new strains with more virulence.